A Comparison of One-to-One and Two-to-One computing in Elementary Mathematics Classrooms: Students’ Perceptions of Their Learning Environment, Attitudes towards Mathematics and Their Mathematics Achievement - Beleckas, Gerard (Curtin University, 2016)
This research compared the learning environment, attitudes towards mathematics, and student achievement in mathematics for classes of fourth and fifth grade students with their own computer or two students sharing a computer. There was no conclusive outcome that one computing environment was better than the other though 2:1 computing may be a viable alternative to 1:1 computing. On several measures, differences in favour of the 1:1 group at pretesting disappeared by the time of post-testing.